SISTEM PENGELOLAAN PERSEDIAAN DAN ASET TETAP YAYASAN PONDOK PESANTREN - Siti Maghfiroh; Permata Ulfah; Irianing Suparlinah; Krisnhoe Rachmi Fitrijati (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
Islamic boarding schools are educational institutions that aim to be a place to learn religious values for students and practice them in everyday life. As a place to gain knowledge, Islamic boarding schools require supplies, both food supplies (food ingredients and prepared meals and supplies for the teaching and learning process (ATK). In addition to supplies, Islamic boarding schools also require assets (infrastructure). Therefore, supplies and assets are used to supporting activities must be managed properly Inventory and asset management goes through several stages, namely: (1) Planning, (2) Procurement, (3) Use, Utilization, Security, Maintenance and Administration, (4) Deletion..